Effects of Macroeconomic Variables on Gross Domestic Product in Saudi Arabia using ARDL model for the period 1993-2019 - Elsharif, Mohamed Sharif Bashir; Babiker, Abdou Aglan (Journal of Economics and Administrative Sciences, 2021)
This paper analyses the relationship between selected macroeconomic variables and gross domestic product (GDP) in Saudi Arabia for the period 1993-2019. Specifically, it measures the effects of interest rate, oil price, inflation rate, budget deficit and money supply on the GDP of Saudi Arabia. The method employs in this paper is based on a descriptive analysis approach and ARDL model through the Bounds testing approach to cointegration. The results of the research reveal that the budget deficit, oil price and money supply have positive significant effects on GDP, while other variables have no effects on GDP and turned out to be insignificant. The findings suggest that both fiscal and monetary policies should be focused on stimulating the role of money supply, oil price management and budget deficits, leading to Saudi Arabia GDP growth targets. In order to respond to domestic and international economic challenges, Saudi Arabia should accelerate the economic diversification plan, reduce dependence on oil, and support non-oil economic sectors